2019
DOI: 10.1016/j.heliyon.2019.e01183
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D in malaria: more hypotheses than clues

Abstract: Vitamin D is a secosteroid hormone regulating calcium and phosphate metabolism, immune response and brain development. Low blood 25(OH)D levels have been reported in patients affected by infectious diseases caused by parasites, including malaria. Despite the high effectiveness of antimalarials, malaria is burdened with high morbidity and mortality, and the search for additional therapies is rapidly growing. Furthermore, available preventive measures have proved to be barely effective so far. Finding new preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 100 publications
(139 reference statements)
4
16
0
Order By: Relevance
“…Malaria co-infection decreases the serum iron level of visceral leishmaniasis patients by 12.69 mcg/dl, the iodine level by 3.78 mcg/l, the serum vitamin A level by 4.8 mcg/dl and the serum vitamin D level by 0.61 ng/ml. This nding was in line with previously published works [54][55][56]. This is due to the ingestion of the nutrients by the parasites, decreases the intake from the host (anorexia), and increases the execration of the nutrients [57][58][59].…”
Section: Discussionsupporting
confidence: 91%
“…Malaria co-infection decreases the serum iron level of visceral leishmaniasis patients by 12.69 mcg/dl, the iodine level by 3.78 mcg/l, the serum vitamin A level by 4.8 mcg/dl and the serum vitamin D level by 0.61 ng/ml. This nding was in line with previously published works [54][55][56]. This is due to the ingestion of the nutrients by the parasites, decreases the intake from the host (anorexia), and increases the execration of the nutrients [57][58][59].…”
Section: Discussionsupporting
confidence: 91%
“…Malaria co-infection decreases the serum iron level of visceral leishmaniasis patients by 12.69 mcg/dl, the iodine level by 3.78 mcg/l, the serum vitamin A level by 4.8 mcg/dl and the serum vitamin D level by 0.61 ng/ml. This nding was supported by other research results [53][54][55]. This is due to the multiple effects of malaria on serum micronutrient levels like ingestion of the nutrients by the parasites, decreases the intake from the host, increases the execration of the nutrients through vomiting, perspiration, etc [56][57][58].…”
Section: Discussionsupporting
confidence: 63%
“…There are ongoing clinical trials of vitamin D in the prevention and treatment of pulmonary infection by utilizing its anti-microbial function and immunomodulatory role (Studies 5-9, Table 1). Our hypothesis is that vitamin D and its analogs might be considered as promising Vitamin D has antimalarial and anti-SLE function Previous in vitro studies have shown that vitamin D has antiplasmodial activity through VDR dependent and independent pathways [67]. The onset and progression of malaria has been shown to involve excessive Th1 cell responses, reduction of Th2 response, and dysfunction of Treg cells, all of which can be limited by the action of vitamin D. Furthermore, vitamin D is known to inhibit the synthesis of key pro-inflammatory cytokines involved in the development of fatal cerebral malaria such as IFN-γ and TNF-α [67].…”
Section: Immunomodulatory Functions Of Extra-renal Vitamin D Metabolimentioning
confidence: 99%
“…Previous in vitro studies have shown that vitamin D has antiplasmodial activity through VDR dependent and independent pathways [ 67 ]. The onset and progression of malaria has been shown to involve excessive Th1 cell responses, reduction of Th2 response, and dysfunction of Treg cells, all of which can be limited by the action of vitamin D. Furthermore, vitamin D is known to inhibit the synthesis of key pro-inflammatory cytokines involved in the development of fatal cerebral malaria such as IFN-γ and TNF-α [ 67 ]. Vitamin D administered after an acute malarial infection increased the survival of diseased mice by at least 15 days compared to non-treated mice through inhibition of IFN-γ and TNF-α synthesis [ 68 ].…”
Section: Main Textmentioning
confidence: 99%